Festival 1000 Tumpeng: Komodifikasi Tradisi, Pariwisata, dan ‘Territoriality’di Gunung Kelud - Edlin Dahniar Alfath; Yogi Setya Permana (Faculty of Social and Political Science, Universitas Airlangga, 2016)
This research explains how tradition can be modified for tourism and political purposes. The tradition that will be elaborated in this essay is